OBJECTIVE EVALUATION OF CPTED PRINCIPLES IN URBAN CONTEXT: A SYNTACTIC ANALYSIS OF HAYATABAD PESHAWAR - Misbahud Din; Ubaid Ullah; Shabbir-u-Qureshi; M. Zeeshan Saqib; Jamal Ahmad (International Journal of Contemporary Issues in Social Sciences, 2023)
With rapid growth of urban population worldwide and specifically in Pakistan, the focus on improving quality of life in cities is more than ever. Numerous varying factors contribute to the fact and a major aspect is that of fear of crime. As a pre-empt, occurrence of crime in the urban fabric is catered to with varying strategies but studies find that spatial configuration and environmental design while being a major contributor do often get neglected in the planning process. This research conducted on Hayatabad Peshawar pinpoints the crime hotspots of the planned area through UCL Depthmap. These hotspots are further investigated to evaluate the status of application of Crime prevention through environmental design (CPTED) strategies in the subject area. The study finds that the said strategies are variably present, where some are catered to, others absent and a number only partially exist.